THE NEXUS BETWEEN SUBNATIONAL DEBT AND ECONOMIC DEVELOPMENT IN NIGERIA - Imandojemu, Kingsley (Quantitative Economics Research, 2019)
The study examined the impact of sub- national debts on economic development. The study covered the period of 1996 to 2018 and data were sourced from Central Bank of Nigeria and Debt Management Office. The study adopted the Fully Modified Ordinary Least Squares and Granger Causality. The Fully Modified OLS was used to investigate the both long run and short run relationships while the Granger Causality was used for direction of causality. The result showed that state government has a statistically significant positive relationship with the growth rate of GDP while Local government debt (LDEBT) and exchange rate had a significant inverse relationship with the growth of GDP. The Interest rate (INT) has positive sign but not significant. The paper recommended that the Federal Government of Nigeria should ensure that   fiscal discipline should be enshrined to curtail diversion of loans received to unproductive channels